2020
DOI: 10.1002/adfm.202001286
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Carrier Lifetime of TiS3 Photoanode by Introduction of S22− Vacancies for Efficient Photoelectrochemical Hydrogen Evolution

Abstract: Recent advances in layered TiS 3 has shown appealing potential for photoelec trochemical hydrogen evolution due to its excellent optical and electronic properties. Here, an excellent photoanode, composed of TiS 3 nanoribbon arrays with moderate S 2 2− vacancies, is proposed to achieve efficient photo electrochemical hydrogen evolution. These unique S 2 2− vacancies are intro duced in the TiS 3 photoanode by a simple vacuum reannealing method, which is inspired by crystal structure analyses of TiS 3 and TiS 2 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…It is demonstrated that the ZrS 3 layer is parallel to the axial direction of NB, which is in favor of charge carrier transport. 34 As shown in the diffuse re ectance UV-vis spectra ( E fb is commonly used to estimate the CBM for a series of n-type semiconductors at the surface in an aqueous environment, which agreed with their theoretically determined values. 1,38,[46][47][48] Previsous stduies on the energy positions of semicondutors have shown that the CBM of zirconium-based sul des is very close to their E fb , 31,47 and therefore the CBM of ZrSS 2-x , and ZrS 1-y S 2-x are higher than the potential for two-electron reduction of O 2 , and their VBMs lie far below the oxidation potential of benzylamine, 12,15,48,49 indicating that these photocatalysts are applicable to the photocatalytic O 2 reduction and benzylamine oxidation.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…It is demonstrated that the ZrS 3 layer is parallel to the axial direction of NB, which is in favor of charge carrier transport. 34 As shown in the diffuse re ectance UV-vis spectra ( E fb is commonly used to estimate the CBM for a series of n-type semiconductors at the surface in an aqueous environment, which agreed with their theoretically determined values. 1,38,[46][47][48] Previsous stduies on the energy positions of semicondutors have shown that the CBM of zirconium-based sul des is very close to their E fb , 31,47 and therefore the CBM of ZrSS 2-x , and ZrS 1-y S 2-x are higher than the potential for two-electron reduction of O 2 , and their VBMs lie far below the oxidation potential of benzylamine, 12,15,48,49 indicating that these photocatalysts are applicable to the photocatalytic O 2 reduction and benzylamine oxidation.…”
Section: Introductionsupporting
confidence: 69%
“…29 The Raman spectra show an obvious red-shift of A g s-s mode by ~5 cm -1 from ZrS 3 to ZrSS 2-x and ZrS 1-y S 2-x , originating from the introduction of S 2 2− vacancies. 34 We also observed a 3 cm -1 red-shift of A g rigid mode from ZrS 3 and ZrSS 2-x to ZrS 1-y S 2-x . Since the A g rigid is correlated to the vibration of quasi-one-dimensional chains in the direction of c axis ( Figure S5a), the shift of A g rigid mode in ZrS 1y S 2-x results from the introduction of S 2− vacancies, which alters the length of Zr-S bonds within each chain.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, apart from the factor of photochemical photocorrosion, which can be dramatically suppressed by the usage of sacrificial agents or surface decoration of passive layers [12][13][14] , the metal sulfides directly employed as photoanodes usually exhibit low photoinduced electron-hole separation efficiencies and sluggish surface water oxidation kinetics [15][16][17][18] , which limits the application of metal sulfides-based photoanodes. The defects in metal sulfide, especially for introducing sulfur vacancies, are evidenced as an effective strategy to enhance the photocatalytic and PEC properties [19][20][21][22] . The trap states introduced by sulfur vacancies can act as capture centers to enable charge carrier separation.…”
mentioning
confidence: 99%